Association between polymorphism in BMP15 and GDF9 genes and impairing female fecundity in diabetes type 2 - Al-Thuwaini, Tahreer (Middle East Fertility Society Journal, 2020)
Background A shortened reproductive period and earlier menopause have been associated with type 2 diabetes. Growth differentiation factor 9( GDF9 ) and bone morphogenetic protein 15 ( BMP15 ) gene mutations have been associated with earlier menopause. Therefore, this study aimed to evaluate the association between BMP15 and GDF9 mutations with impairing female fecundity in diabetic patients. The study subjects comprised 90 female diabetic patients and 60 female healthy controls. The physio-biochemical analysis was measured using enzymatic determination. A single-strand conformation polymorphism (SSCP) protocol was utilized to assess the pattern of genetic variations. Results Genotyping analysis of the BMP15 gene showed a heterogeneous pattern with the presence of two genotypes: AA and AC genotypes. Five novel missense single nucleotide polymorphisms (SNPs) were identified in the BMP15 gene: four SNPs detected in both genotypes, and Met4Leu, a specific SNP, was detected only in the AC genotype. Cumulative in silico tools indicated a highly deleterious effect for the Met4Leu on the mutant protein structure, function, and stability. Diabetes patients showed a significantly higher frequency of genotype AC. The physio-biochemical analysis of fasting plasma glucose (FBG), glycosylated hemoglobin (HbA1c), and luteinizing hormone (LH) were significantly higher ( P < 0.05) in AC genotype than AA genotype. Conclusions The current research provides the first indication regarding the tight association of BMP15 polymorphism with the impairing female fecundity in the diabetic. A pivotal role is played by the novel (Met4Leu) SNP that can be used as a predictor for the impairing female fecundity of diabetes, while no polymorphism was found in exon 4 of the GDF9 gene.